2017
DOI: 10.1002/ejoc.201700974
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Free Synthesis of Cyanoformamides from Carbamoyl Imidazoles

Abstract: A straightforward and solvent‐free synthesis of various secondary and tertiary cyanoformamides from carbamoyl imidazoles and TMSCN has been developed. Both cyclic and acyclic carbamoyl imidazoles react smoothly to form the relevant cyanoformamides in excellent yields, often within minutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Recently, other more direct synthetic methods have been developed (Scheme 2). 23–29 For instance, Muñoz reported that the reaction of primary amines with tetramethylphenylguanidine and cyanophosphonates at −10 °C under an atmosphere of CO 2 furnishes cyanoformamides in good yields. 23 Dong and co-workers 24 employed phosphoryltrichloride (POCl 3 ) to convert 1-acyl-1-carbamoyl oximes to cyanoformamides, while concurrently Wu and co-workers 25 reported an eco-friendly method for the conversion of 2-oxoaldehydes into cyanoformamides using iodosobenzene diacetate (IBD) as oxidant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, other more direct synthetic methods have been developed (Scheme 2). 23–29 For instance, Muñoz reported that the reaction of primary amines with tetramethylphenylguanidine and cyanophosphonates at −10 °C under an atmosphere of CO 2 furnishes cyanoformamides in good yields. 23 Dong and co-workers 24 employed phosphoryltrichloride (POCl 3 ) to convert 1-acyl-1-carbamoyl oximes to cyanoformamides, while concurrently Wu and co-workers 25 reported an eco-friendly method for the conversion of 2-oxoaldehydes into cyanoformamides using iodosobenzene diacetate (IBD) as oxidant.…”
Section: Introductionmentioning
confidence: 99%
“… 26 At the same time, Schwartz's group described solvent-free access to secondary and tertiary cyanoformamides from TMSCN and carbamoyl imidazoles. 27 Recently, cyanoformamides were prepared from N , N -disubstituted aminomalononitriles 28 with CsF as the promoter and in another study, 4,5-dioxo-imidazolinium cation activation of 1-acyl-1-carbamoyl oximes was used. 29 Electrochemical synthesis of cyanoformamides was also reported starting from trichloroacetonitrile and secondary amines mediated by heptamethyl cobyrinate, a B 12 derivative.…”
Section: Introductionmentioning
confidence: 99%
“…36 The cyanoformamide 30 has been prepared as an electrophilic carbonyl source to incorporate the cubyl amide directly. 37 The nitrile 31 has also been prepared and used to generate isoxazole cubane 32 with a primary amine for further functionalization. 28 Alternatively, the imidazole heterocycle 33 can be generated, also with a nucleophilic nitrogen atom.…”
Section: Monosubstituted Building Blocksmentioning
confidence: 99%
“…In the case of 27 , the Boc and methyl ester protected compound can undergo chiral (enantioselective) HPLC separation that affords, following deprotection, (+)- and (−)- 27 . The cyanoformamide 30 has been prepared as an electrophilic carbonyl source to incorporate the cubyl amide directly . The nitrile 31 has also been prepared and used to generate isoxazole cubane 32 with a primary amine for further functionalization .…”
Section: Synthesis Of Cubane and Monosubstituted Building Blocksmentioning
confidence: 99%
“…Since the carbonyl carbon atom of the carbonylimidazole moiety is easily attacked by a nucleophile the imidazole group readily dissociates. The N-substituted carbonylimidazoles have favorable reactivity and can be widely used in the synthesis of various valuable products such as ureas [63][64][65][66][67][68][69][70], carbamates [66,[71][72][73][74], thiocarbamates [66], and cyanoformamides [75]. However, all of these works are primarily focused on the substitution reaction of N-substituted carbonylimidazoles.…”
Section: Introductionmentioning
confidence: 99%